Synthesis of low temperature firing scheelite-type BaWO4 microwave dielectric ceramics with high performances. Issue 1 (1st January 2022) - Gui, Ling; Yang, Hongcheng; Zhao, Qian; Li, Enzhu
Abstract: The synthesis of scheelite-structured BaWO4 ceramics at low temperatures using a Li2 O–B2 O3 –BaCO3 –CuO (LBBC) glass frit is reported in this study. Composite ceramics with the chemical formula BaWO4 - x LBBC ( x  = 0.25, 0.5, 1, and 2 wt%) were synthesized via the standard solid-phase method. A compact BaWO4 matrix containing glass crystallized when sintered at 850 °C for only 30 min. The BaWO4 ceramic with 1 wt% LBBC glass exhibits optimum microwave dielectric performance with Q ×  f  = 58, 855 GHz, εr  = 8.33, and τ f  = −61.43 ppm/°C. A results of XRD and SEM analyses, microwave properties and the liquid-phase sintering mechanism for the ceramics are presented. Highlights: The Q ×  f  value remained excellent for 58855 GHz while the temperature decreased from 1100 °C to 850 °C. The compound was still the pure BaWO4 phase. The shorter soaking time (30min) can effectively reduce the energy consumption.